2023
DOI: 10.1109/access.2023.3270803
|View full text |Cite
|
Sign up to set email alerts
|

State-Based Decoding of Continuous Hand Movements Using EEG Signals

Abstract: Recently, the advent of the non-invasive brain-computer interface (BCI) for continuous decoding of upper limb motions opens a new horizon for motor-disabled people. However, the performance of discrete-decoding BCIs based on discriminating different brain states are still more robust. In this study, we aimed to cascade a discrete state decoder with a continuous decoder to enhance the prediction of hand trajectories. EEG data were recorded from nine healthy subjects performing a center-out task with four orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In this context, some studies have reported classification of executed movements vs rest, where Kaiser et al reported an Acc close to 0.70 for classifying hand movements vs rest [39]. Hosseini et al used CSP based methods to design a rehabilitation device based on continuous 2D hand motion classification and decoding, where the classification results obtained an Acc close to 0.97 [15]. However, these two approaches have been used for the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, some studies have reported classification of executed movements vs rest, where Kaiser et al reported an Acc close to 0.70 for classifying hand movements vs rest [39]. Hosseini et al used CSP based methods to design a rehabilitation device based on continuous 2D hand motion classification and decoding, where the classification results obtained an Acc close to 0.97 [15]. However, these two approaches have been used for the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis was performed to verify the appropriate number of subjects for model generalization, based on the results reported in the literature. To address this, a G * power d = 2.13, a power of 0.90, and a value of α = 0.05 were used as recommended in previous studies focused on EEG and AM [15,19]. The minimum number of subjects computed by the G * Power software for the Wilcoxon signed-rank test was seven; however, a deviation of 20% was considered as the final sample size.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten healthy individuals participated in this study (six male and four female), ranging in age from 21 to 48 years (29 ± 9), and without any neurological, psychological or other health conditions reported. The statistical power of the sample size was estimated using G*power software to suggest whether the results of the performance metrics can be compared with the literature [39,40]. Wilcoxon signed rank was used with a value of α = 0.05, an effect size of d = 2.13, and a sample size of n = 10.…”
Section: Experimental Protocol 221 Participantmentioning
confidence: 99%